Período de formação do cacho e biorreguladores na produção e qualidade da banana ‘Grande Naine - Lima, Juliana Domingues [UNESP]; Rosa, Jéssica Santa [UNESP]; Da Silva Moraes, Wilson; da Silva, Silvia Helena Modenese-Gorla [UNESP]; Rozane, Danilo Eduardo [UNESP]; Gomes, Eduardo Nardini [UNESP] (FapUNIFESP (SciELO), 2015)
The objectives of this study were to determine the effect of climatic conditions during the period of bunch formation and growth regulators on yield and quality of banana ‘Grande Naine’. The experiment was conducted in a completely randomized split plot with six replications. It was considered the plots, and the periods of bunch formation, summer and autumn. In the subplots it was considered the growth regulators: two applications were made with water, gibberellin (GA3, 200mg L-1), auxin (2.4-D, 10mg L-1), cytokinin (TDZ, 150mg L-1) and a mixture of gibberellin, auxin and cytokinin (AG3, 56.3mg L-1; AIB, 56.3mg L-1 and ZEA, 101.3mg L-1). Periods of bunch formation influence the number of hands, the size, shelf life, pH, titratable acidity, soluble solids and titratable acidity ratio and the firmness of the fruit. The mixture of growth regulators increase the weight of the bunch and the 4th hand bunches formed in the summer.
Period of bunch formation and growth regulators on yield and quality of banana ‘Grande Naine’
Keywords: Auxin; Cytokinin; Gibberellins; Musa spp; Source-sink relationship